Democratic Transition in Southern Mediterranean Countries: A Theoretical -Practical Approach - KHELALFA, Hadjer (Journal of Human Sciences, 2025)
The article seeks to clarify the diverse theoretical frameworks and perspectives that underpin the dynamics of democratic transition. It examines the structure of this transition, considering its inputs, catalysts, and outcomes, with a particular focus on the consolidation of democracy during the post-transition period. The aim is to forge a relational synthesis, integrating theoretical constructs with their practical applications in the restoration of state legitimacy and its institutions. This synthesis prioritizes the upholding of rights and freedoms, their active practice, and the pursuit of social justice.